Low-cost commercial graphite-rich pencils subjected to electron irradiation for passive radiation dosimetry - Siti Nurasiah, Mat Nawi *; Khandaker, Mayeen Uddin *; S.F. Abdul, Sani; Lam, S.E.; Ung; Almugren, K.S.; Bradley, D.A. * (Elsevier, 2022)
Various thicknesses of 2B grade polymer pencil lead graphite (PPLG) were used in the present study, which focussed on the alteration in crystalline lattice and the structural defect caused by the electron irradiation dosage ranging from 0.5 to 20 Gy delivered by an Elekta HD Linac. The fundamental trap parameters i.e. kinetics order (b), activation energy (E), and frequency factor (s) of the PPLG samples have been estimated using the initial rise and peak shape approaches by fitting the thermoluminescence (TL) glow peaks of the PPLG samples exposed to 20 Gy. The lifetime of the TL glow peak is also presented, which provides information on the stability of the TL signal at maximum temperatures. Raman, Photoluminescence (PL), and X-ray diffraction (XRD) spectra are being used to observe the structural changes that have occurred as a result of the radiation doses. These spectroscopies offer an understanding of the physical parameters that are related to the defects and taking part in the luminescence process. When all of the data are taken into account, it is anticipated that 0.3 mm PPLG is an effective material for dosimetry. The results of these lines of research are intended to educate the innovation of versatile graphite radiation dosimeters as a low-cost efficient system for radiation detection. The studied PPLG offers tissue equivalence as well as high spatial resolution, both are desirable criteria for a material to be used in the monitoring of ionising radiation or a variety of medical applications.